Choosing the unstable: Dancing through the mid-career - Bennett, Dawn; Pollitt, J. (European Association of Conservatoires AEC, 2009)
Whilst professional instability is a lifelong challenge for dance artists, it is in mid career that instability becomes particularly problematic and the issue of sustainability comes to the fore. Mid-career artists build increasingly diverse protean careers in a bid to generate stability whilst dealing with unpredictable work patterns, aging bodies, and increased financial, family and future responsibilities. In addition to this is the sense of physical and emotional loss experienced when the fundamental need to dance is not being fully met. In this study we underscore these big picture issues with a more personal dialogue with three Australian mid-career dance artists. Through these case studies we examine the constant negotiation, reassessment and instability inherent in dance careers. Our research reveals that 'putting the body down' often entails putting down work, status and identity.